Less compelling than it seems: rethinking the relationship between aggregate FDI inflows and national competitiveness - Lukas Linsi (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2016)
Levels of FDI inflows are commonly regarded as an unmistakable cause and outcome of a country's economic "competitiveness". This Perspective argues that the connections underlying such views are not as straightforward as they might seem, and calls for a more nuanced analysis of the economic meaning of FDI inflows.
Keywords: 330